English Teachers’ Experiences in Teaching with Limited Instructional Media: A Case Study at SMPN 2 Kuripan - Sartika, Santi; Yusra , Kamaludin; Lestari, Yuni Budi (Jurnal Ilmiah Profesi Pendidikan, 2026)
This study explores the lived experiences of English teachers in teaching with limited instructional media at SMPN 2 Kuripan. The purpose of this study is to investigate teachers’ instructional experiences, emotional and professional responses, and reflective practices in a media-limited classroom context. This research employed a qualitative case study design supported by classroom ethnographic techniques. Data were collected through semi-structured interviews, classroom observations, and document analysis, and were analysed using ethnographic data analysis procedures involving coding, theme development, and interpretation. The findings reveal that English teachers experienced instructional and emotional challenges due to limited instructional media; however, they demonstrated strong teacher agency, pedagogical flexibility, and creativity by utilizing available resources and implementing student-centred activities. These experiences contributed to emotional resilience, continuous reflection, and the development of teachers’ professional identity. In conclusion, effective English teaching in media-limited contexts depends more on teachers’ professional agency, reflective practice, and emotional adaptability than on the availability of instructional technology.